Археологічні, історичні дані про системні зміни якості населення та закономірності історичного розвитку - Кислий, О.Є. (Археологический альманах, 2009)
S.N. Bibikov one of the first and parallel with other scientists (N.P. Gryaznov, V.M. Masson, V.I Dovzhenok, J.G.D. Clark, C. Renfrew, S.R. Binford, other) developed new directions of reconstruction archaeology. Thus, he paid a regard to that is certain independent dialectics in the process of development of population and primitive technologies.